2016
DOI: 10.3758/s13414-016-1110-y
|View full text |Cite
|
Sign up to set email alerts
|

Feature-based attention across saccades and immediate postsaccadic selection

Abstract: Before each eye movement, attentional resources are drawn to the saccade goal. This saccaderelated attention is known to be spatial in nature, and in this study we asked whether it also evokes any feature selectivity that is maintained across the saccade. After a saccade toward a colored target, participants performed a postsaccadic feature search on an array displayed at landing. The saccade target either had the same color as the search target in the postsaccadic array (congruent trials) or a different color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 51 publications
(76 reference statements)
0
12
0
Order By: Relevance
“…However, a limitation of the Eymond et al (2016) study is that the results may have been caused by a failure to generalize feature representations across two substantially different tasks (i.e., simple saccadic orienting and full-array visual search), rather than reflecting the mechanisms inherent to gaze control. Substantial post-saccadic changes in a display can provide unambiguous evidence that the scene has changed, supplanting the processes designed to establish transsaccadic correspondence (Deubel et al, 1998;Deubel, Schneider, & Bridgeman, 1996;Poth & Schneider, 2016;Tas, Moore, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a limitation of the Eymond et al (2016) study is that the results may have been caused by a failure to generalize feature representations across two substantially different tasks (i.e., simple saccadic orienting and full-array visual search), rather than reflecting the mechanisms inherent to gaze control. Substantial post-saccadic changes in a display can provide unambiguous evidence that the scene has changed, supplanting the processes designed to establish transsaccadic correspondence (Deubel et al, 1998;Deubel, Schneider, & Bridgeman, 1996;Poth & Schneider, 2016;Tas, Moore, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies found that the shift of spatial attention to the target before the saccade failed to generate feature-based biases; there was no presaccadic perceptual enhancement at other locations sharing target features (Jonikaitis & Theeuwes, 2013;White, Rolfs, & Carrasco, 2013; but see Born, Ansorge, & Kerzel, 2012). More directly relevant to trans-saccadic processes, Eymond, Cavanagh, and Collins (2016) tested feature-based selection after the saccade using a combined eye movement and singleton search task. The participants executed a saccade to a colored object appearing in isolation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we aimed to determine whether feature-based attention, which processes features independently of their location, could also take part in establishing visual stability across saccades. Some studies have examined the link between the attentional deployment and the visual properties of the saccade target and found no interplay between them (Eymond, Cavanagh, & Collins, 2016;Jonikaitis & Theeuwes, 2013;White, Rolfs, & Carrasco, 2013). Here we tested feature-based selection independently of the attentional resources allocated to the saccade target.…”
Section: Introductionmentioning
confidence: 97%
“…The saccade target itself benefits from prioritized encoding into VSTM (Irwin & Gordon, 1998), and a variant of the object-file theory proposes that a search process attempts to locate the target object after every saccade, based on remembered visual features of the presaccadic object (Deubel, Schneider, & Bridgeman, 2002;McConkie & Currie, 1996). However, attempts to measure such a search have not been successful (Eymond, Cavanagh, & Collins, 2016;Jonikaitis & Theeuwes, 2013). According to the VSTM account of visual stability, establishing object correspondence across a saccade depends on similarity between the visual features before and after the saccade.…”
mentioning
confidence: 99%